Technology Acceptance Model (TAM) applied to a Disciplinary Social Network for online psychology students (Research, Society and Development, 2024)
Social networks have been present in people's daily lives to share information and communicate with family and friends. In the educational field, they have come up with commonly used social networks such as Facebook and Twitter-X, however, these networks have been accused of accessing user data without their consent for marketing purposes. In this scenario, there are open-source social networks that can be used in the educational field, thus creating Disciplinary Social Networks (Disciplinary SN). Our research objective is to evaluate the Attitude, Intention to Use, Perceived Usefulness, Ease of Use, Trust and Perceived Risk of a Disciplinary Social Network. For this, we used a modified Technology Acceptance Model (TAM) instrument. The sample consisted of 211 university students from an online psychology degree and users of a Disciplinary Social Network based on the Mastodon social network. The results obtained show considerably high means in all scales of the modified TAM instrument, except for perceived risk, which obtained a low mean. It is concluded that the Disciplinary Social Network was perceived as a safe and reliable environment, with a low perception of risk, in contrast to the findings of other authors who evaluated the same elements in commonly used social networks such as Facebook.